The Effect of Capital Adequacy and Earning Asset Quality on Profitability at PT. BPRS Harta Insan Karimah Makassar - Muhammad Anugrah Ardhana (Jurnal Economic Resource, 2022)
This study aims to determine and analyze the effects of capital adequacy and the quality of productive assets (KAP) on profitability. The object of this research is PT. BPRS Harta Insan Karimah Makassar, where researchers took data in the form of financial statements for the 2017–2019 period as a sample using the purposive sampling method. The data collection method in this research uses the literature study method and the documentation method. Normality, multicollinearity, autocorrelation, and heteroscedasticity tests are used to analyze test requirements. The analytical method used is multiple regression analysis. The results of this study indicate that: (1) capital adequacy has a significant but not significant effect on profitability; (2) product asset quality (KAP) has a significant effect on profitability; and (3) capital adequacy and the quality of productive assets (KAP) together have a significant effect on profitability at PT. BPRS Harta Insan Karimah Makassar period 2017–2019.